Assessing the Cost of Protection in Vietnam after Becoming WTO's member - Nguyen, Anh Thu (ĐHKT, 2016)
Since the economic reform in 1986, Vietnam has experience extremely quick integration into the world market. Trade volume has increased sharply and the composition of Vietnam trading partners has broadened. Trade turnover in 1990 was roughly 6.2 billion USD, however, in 2005 it reached 69.2 billion USD and that of 2008 has been 143.4 billion USD.